DAMAGE MORPHOLOGICAL PARAMETERS - Chermant, Jean-Louis; Boitier, Guillaume; Darzens, Severine; Coster, Michel; Chermant, Liliane (Image Analysis and Stereology, 2011)
This paper shows how it is possible to characterize and quantify the damages in materials using classical tools of automatic image analysis. Examples presented concern ceramic matrix composites, i.e. high tech materials. It gives important information to support the deformation and rupture mechanism of materials under mechanical solicitations.